Peyronie's Disease and Mechanotransduction: An In Vitro Analysis of the Cellular Changes to Peyronie's Disease in a Cell‐Culture Strain System. (19th February 2013) - Chung, Eric; De, Ling; Solomon, Matthew; Brock, Gerald B.
Abstract Introduction Penile traction therapy (PTT) has gained considerable popularity as a noninvasive treatment option in Peyronie's disease (PD) to improve penile curvature and length. However the exact mechanism of action of PTT is unknown and as yet unproven. Aim Using a cyclic strain culture system, we investigate the cellular changes to the tunical tissues following equibiaxial tractional forces. The observed protein alteration following mechanical traction should replicate the changes observed in tunical tissue following PTT. Methods FlexcellTM FX‐5000TM Tension Plus system (FlexcellTM International Corporation, McKee‐sport, PA, USA) is a pressurized chamber system that allows for sustained and dynamic application of hydrostatic pressure to cellular culture. Primary cell cultures from PD and normal tunical tissue (control) were sub‐cultured on BioFlex‐ProNectin plate 1 × 106 (Flexcell International Corporation, Hillsborough, NC, USA) for 24 hours and exposed to FlexcellTM sinusoidal strain of 18% at 1 Hz (strained group) on the biaxial plates for 24 hours under 37°C in a 5% CO2 atmosphere. Main Outcomes Measures Immunohistochemistry (IHC) stains and Western blot assays between strained and nonstrained (control) cells. Results Significant increase in smooth muscle α‐actin, β‐catenin, and Hsp 47 proteins were measured in the PD group compared with control group. IHC staining revealed a decrease in α‐actin staining while Western blot assay showed an increase in metalloproteinase‐8 expression with no measured change in β‐catenin level in the strained PD group. Conclusions This novel study of cells derived from diseased and normal human tunica albuginea cultured in a mechanical strained environment provides good scientific evidence for the use of penile traction device in Peyronie's plaque remodeling.